Preparing mental health providers for the future: the case for moving beyond the elective telehealth course to integrating telehealth training throughout the curriculum - Wibberly, Kathy Hsu (Frontiers in Psychology, 2024)
In the wake of the COVID-19 Public Health Emergency and the consequent surge in telehealth adoption, the mental healthcare landscape has undergone a profound transformation propelled by rapid technological advancements. This paradigm shift necessitates a fundamental re-evaluation of the training methodologies for mental health providers. To effectively leverage the potential of telehealth and empower mental health professionals with the requisite skills for utilizing digital tools, a comprehensive integration of telehealth into graduate program curricula is imperative. This article proposes practical strategies for seamlessly incorporating telehealth into both the theoretical and practical facets of graduate education. These strategies encompass a holistic understanding of technological platforms, ethical considerations, legal and regulatory frameworks, cultural competence, digital equity challenges, as well as clinical assessment and therapeutic approaches. The author concludes by issuing a call to action, urging mental health professions training programs and their accrediting bodies to proactively redefine their approach, ensuring mental health providers are adequately prepared for the future.